On the relationship between dance and propaganda - the case of Sergei Polunin - Reglińska-Jemioł, Anna (The phenomena of propaganda and manipulation in the press, radio, television, and internet. Volume II, 2023)
In the context of the growing scale of indoctrination of the young generation in Russia, manifested by the fascination of Vladimir Putin, the case study of Sergei Polunin (Sergei Polunin), a world-famous ballet dancer born in 1989 in Kherson (Ukraine) and a declared supporter of Putin, takes on a special dimension. The tattoo showing the face of the Russian leader (placed right next to the heart, on the chest), which Polunin decided to make in 2018, became an open manifestation of the artist’s views. After Russia's invasion on Ukraine, and even after the aggressor entered his hometown, the dancer did not react, did not declare, and did not even issue a binding short comment. The case of a ballet soloist provokes further questions in the course of the critical discourse on the art of dance - can ballet be a “commercial, advertising product”? In what language does this choreography appeal to the audience? And finally, can its artistry serve propaganda? While analyzing the process of cultural transmission from a historical perspective, a clear tendency to proclaim specific ideas through choreography might be noticed.